Event-Triggered Sliding Mode Control A New Approach to Control System Design - Bandyopadhyay, Bijnan (Studies in Systems, Decision and Control,, 2018)
This edited monograph provides a comprehensive and in-depth analysis of sliding mode control, focusing on event-triggered implementation. The technique allows to prefix the steady-state bounds of the system, and this is independent of any boundary disturbances. The idea of event-triggered SMC is developed for both single input / single output and multi-input / multi-output linear systems. Moreover, the reader learns how to apply this method to nonlinear systems. The book primarily adresses research experts in the field of sliding mode control, but the book may also be beneficial for graduate students.